(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
In spite of consumers’ awareness and consciousness regarding environmental issues, there is a lack of purchase of green products by consumers. They are showing concern for environment; but they are not purchasing green products. There are various factors which negatively affect the purchase of green products by consumers. So this study was conducted with an objective to explore the factors restricting rural consumers to buy green FMCG products. For this purpose data were collected from 200 respondents. By applying factor analysis; ten factors were explored regarding restricting the rural consumers to buy green FMCG products. These factors include Lack of knowledge and promotion; Uncaring Behaviour; Inefficacy of green products; Negative attitude and speciousness regarding advertisements claims; Negligence towards green products; Ambiguity in claims and cost factor; lack of promotional incentives and quality; Self-inefficacy and lack of belief; Ineffective labeling and Complex exercise.